Improvement of Red Rice Yield by Changing from Conventional to Aerobic Irrigation Systems Intercropped with Soybean at Different Dates - Wangiyana, Wayan; Farida, Nihla; Zubaidi, Akhmad; Sri Suliartini, Ni Wayan (International Journal of Environment, Agriculture and Biotechnology, 2021)
Previous studies reported that intercropping rice with legume crops under aerobic systems increased growth and yield of rice compared with monocropped rice. This study aimed to examine the effects of rice cultivation techniques and patterns of rows on growth and yield of red rice with special objective to examine if intercropping red rice with soybean relay-planted between double or triple rows of rice on raised-beds under aerobic irrigation system can produce higher yield than the conventional one. The experiment was conducted in Narmada (West Lombok, Indonesia), arranged according to Split Plot design with two treatment factors, i.e. rice row patterns as the main plots (P1= double, P2= triple rows) and techniques of rice cultivation (Tc= conventional rice, T0= irrigated aerobic rice system (ARS) without intercropping; T1= relay-planting soybean 1 week, T2= 2 weeks, T3= 3 weeks after seeding the pre-germinated red rice seeds). Results indicated that between the two treatment factors, techniques of growing rice resulted in significant effects on more variables compared with the patterns of rice rows, but there were significant interaction effects on leaf number per clump at anthesis and grain yield per clump. Based on the main effects, tiller number, filled panicle number and grain yield per clump and harvest index were significantly higher on red rice plants grown in irrigated aerobic systems intercropped with soybean compared with those in aerobic monocropped or conventional systems, with the highest grain yield average of 53.76 g/clump in T3, 29.04 g/clump in T0 and only 17.45 g/clump in Tc treatment, and based on the interaction effects, the highest average of grain yield was on red rice plants in the T3 treatment under triple-row pattern (57.58 g/clump) and the lowest was on conventional plot (Tc) under double-row pattern (16.53 g/clump).